Data Warehousing and Knowledge Discovery 14th International Conference, DaWaK 2012, Vienna, Austria, September 3-6, 2012. Proceedings - Cuzzocrea, Alfredo; Dayal, Umeshwar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 14th International Conference on Data Warehousing and Knowledge Discovery, DaWaK 2012 held in Vienna, Austria, in September 2012. The 36 revised full papers presented were carefully reviewed and selected from 99 submissions. The papers are organized in topical sections on data warehouse design methodologies, ETL methodologies and tools, multidimensional data processing and management, data warehouse and OLAP extensions, data warehouse performance and optimization, data mining and knowledge discovery techniques, data mining and knowledge discovery applications, pattern mining, data stream mining, data warehouse confidentiality and security, and distributed paradigms and algorithms.
Data Warehouse Design Methodologies -- ETL Methodologies and Tools -- Multidimensional Data Processing and Management -- Data Warehouse and OLAP Extensions -- Data Warehouse Performance and Optimization -- Data-Mining and Knowledge-Discovery Techniques -- Data-Mining and Knowledge-Discovery Applications -- Pattern Mining -- Data Stream Mining -- Data Warehouse Confidentiality and Security -- Distributed Paradigms and Algorithms.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Information systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; User Interfaces and Human Computer Interaction